Influence of political stability on the stock market returns and volatility: GARCH and EGARCH approach - Wajid Alim; Naqib Ullah Khan; Vince Wanhao Zhang; Helen Huifen Cai; Alexey Mikhaylov; Qiong Yuan (Financial Innovation)
Abstract Political instability has increased drastically in Pakistan during the last few decades. This may intensify the fear of investors and eventually affect investment decisions. Therefore, the stock market’s reaction to political stability must be explored and appropriate policy measures should be prescribed. This paper examines the effect of political stability on stock market returns and volatility using time series data from Pakistan for the period from January 02, 2004, to May 31, 2018. The study uses the Generalized Autoregressive Conditional Heteroskedastic (GARCH) and Exponential Generalized Autoregressive Conditional Heteroskedastic (EGARCH) models to achieve the main objectives. The findings of the GARCH and EGARCH models confirm that political stability has a positive and significant influence on both stock market returns and volatility in Pakistan. In addition, the EGARCH findings indicate that negative shock (political instability) creates more volatility in the stock market than positive shock (political stability). The results of this study reveal that financial market investors are affected more by political instability. In conclusion, this study suggests that political stability is an essential factor affecting financial market volatility, and it leads to stable financial markets. It also emphasizes that political instability needs to be resolved to achieve stable financial markets.